Improvement of the methodology of the audit airlines (Eurasian Journal of Ecology, 2016)
This article provides a solution to the problem of formation of strategy and tactics of improving aviation safety through auditing companies. Developed categorical apparatus and form a model of the methodology of audit in the airlines. The presented theoretical and practical results will facilitate establishing safety of the population.
Keywords: audit; autocompanies; analysis